SYSTEMATIC LITERATURE REVIEW LEADERSHIP STYLE TO EMPLOYEE PERFORMANCE IN MANUFACTURING COMPANY - Ramdani Ramdani; Yanneri Elfa Kiswara Rahmantya; April Laksana; Hadi Kurniawanto (SEAN Institute, 2023)
A true leader can create a good atmosphere and culture where his subordinates can show and realize all their abilities to work optimally. A leader's leadership style has an important role to organize, manage and direct his team to achieve the goals and targets of the organization or company he leads. A leader's leadership style will significantly influence the achievement of his team's performance or what we call employee performance. This research aims to identify and analyze leadership styles that can influence employee performance. Many journals and studies discuss the effect of leadership style on employee performance, so a review of journal papers that discuss this is necessary. The method used in this study is a Systematic Literature Review (SLR) of published journal papers from 2022-2023. There are three Research Questions (RQ) defined in this study. The final results obtained from several journals studied show that a leader's leadership style dramatically influences the achievement of employee performance, and what is very dominant here is transformational leadership which has a very positive effect on employee performance. With the results of this study, we hope that it can provide knowledge and education to all leaders that the quality of work or employee performance is greatly influenced by the style and ability of the leader in managing and controlling the company he leads and one of the best is the leadership style of transformational leadership.